Phaeochromocytoma in multiple endocrine neoplasia type 2: RET codon-specific penetrance and changes in management during the last four decades - Mucha, Lena; Leidig-Bruckner, Gudrun; Bruckner, Thomas (Clinical endocrinology, 2017)
Objectives We describe phaeochromocytoma (phaeo) penetrance in multiple endocrine neoplasia type 2 (MEN2) according to RET protooncogene-specific mutations and report changes in phaeo diagnosis and management from 1968 to 2015. Design This retrospective chart review included 309 MEN2 patients from one specialized ambulatory care centre. Phaeo patients were categorized by diagnosis date: early, 1968-1996, n=40, and recent, 1997-2015, n=45. Results Phaeochromocytoma was diagnosed in 85/309 patients with RET mutations in the following exons (phaeos/all carriers, %): exon 11 (56/120, 46.6%); exon 16 (7/17, 41.2%), exon 10 (14/47, 29.8%), and exon 13-15 (2/116, 1.7%). Age at phaeo diagnosis differed according to affected exon: 21.9±1.5 years, exon 16; 34.1±11.6 years, exon 11; and 41.8±8.8 years, exon 10. Age-related phaeo penetrance differed among five amino acid substitutions at codon 634 and was highest for Cys634Arg and Cys634Tyr. Age at diagnosis was 34.4±11.6 years in the early and recent groups. Phaeochromocytoma and medullary thyroid carcinoma (MTC) were diagnosed synchronously in 21/40 (early) vs 8/45 (recent) and metachronously in 19/40 vs 37/45 cases. Diagnostic methods significantly changed from clinical (22/40 vs 4/45) to biochemical and/or imaging based (14/40 vs 35/45). Phaeochromocytoma diameter at diagnosis was 4.6 vs 2.6 cm. Conclusion Phaeochromocytoma penetrance and age of diagnosis are highly correlated with MTC aggressiveness based on RET mutation status, with higher penetrance and younger age of diagnosis associated with more aggressive MTC. Penetrance steadily increases with age. At-risk patients require lifelong follow-up.
Gesehen am 23.05.2018